Strategi Pembelajaran dalam Meningkatkan Motivasi Belajar Siswa - Muhammad Alfi; Fadhilatul Muharram; Gusmaneli Gusmaneli (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Learning activities will be successful if students have motivation to learn. Therefore, the article we wrote aims to better understand and test the influence of learning strategies implemented by teachers in increasing students' learning motivation. In achieving the goal of increasing student motivation, there needs to be better efforts in selecting and implementing learning strategies that are appropriate to the competencies to be achieved. The research we conducted used a descriptive analysis approach through data collection methods. This data was collected using literature studies through articles, journals and books. To increase students' learning motivation, it is necessary to choose appropriate learning strategies by considering the characteristics of the objectives and content of the field of study. The results of the analysis show that there is a big influence that learning strategies have on increasing student learning motivation. This influence has an impact on student learning outcomes for the better. Each learning strategy has a different influence on student learning motivation. Applying correct learning strategies also increases students' understanding of the learning content.